A Novel Image Fusion Method Via Ratio Weighted and Condition Weighted Based on Shearlet Transform (Journal of Fiber Bioengineering and Informatics, 2015)
In this paper, a new image fusion method is proposed based on the shearlet transform. The new imageis reconstructed by image fusion, which provides richer visual information than the original images.The image could be decomposed by shearlet transform in any scale and any direction, and the detailinformation can be caught easily. The multi-scale and multiple directions decomposition coefficientsare obtained through shearlet transformation. The fusion results are analyzed and compared withthe measurement of human visual system and objective evaluation. The experiment results show theadvantages of the new fusion method compare to other classical fusion algorithm. The simulation resultsof the multimodal images are adopted to demonstrate that the algorithm based on shearlet transform isable to obtain fused images of higher clarity and complementary information compared with any othermethods.